Advanced Technologies for Quantum Photonic Devices Based on Epitaxial Quantum Dots. Issue 2 (11th October 2019) - Zhao, Tian Ming; Chen, Yan; Yu, Ying; Li, Qing; Davanco, Marcelo; Liu, Jin
Abstract: Quantum photonic devices are candidates for realizing practical quantum computers and networks. The development of integrated quantum photonic devices can greatly benefit from the ability to incorporate different types of materials with complementary, superior optical or electrical properties on a single chip. Semiconductor quantum dots (QDs) serve as a core element in the emerging modern photonic quantum technologies by allowing on‐demand generation of single‐photons and entangled photon pairs. During each excitation cycle, there is one and only one emitted photon or photon pair. QD photonic devices are on the verge of unfolding for advanced quantum technology applications. This review is focused on the latest significant progress of QD photonic devices. First, advanced technologies in QD growth are discussed, with special attention to droplet epitaxy and site‐controlled QDs. Then, the wavelength engineering of QDs via strain tuning and quantum frequency conversion techniques is overviewed. The discussion is extended to advanced optical excitation techniques recently developed for achieving the desired emission properties of QDs. Finally, the advances in heterogeneous integration of active quantum light‐emitting devices and passive integrated photonic circuits are reviewed, in the context of realizing scalable quantum information processing chips. Abstract : Quantum photonic devices are candidates for realizing practical quantum computers and networks. This review reports the latest significant progress of quantum dot (QD) photonic devices, including advanced technologies in the QD growth, the wavelength engineering, and the optical excitation. Advances in heterogeneous integration of active quantum light‐emitting devices and passive integrated photonic circuits are also discussed.